Study of Ismuba Subjects on the Implementation of Religious Students - Sofiaty, Ani; Wage, Wage; Darojat, Darojat (Journal La Sociale, 2025)
This study explores the implementation of ISMUBA (Islamic Religious Sciences, Muhammadiyah Ideology, and Arabic) subjects at SMK Muhammadiyah Bumiayu and its role in shaping students' religious behavior. Using a qualitative descriptive approach, the research examines the methods, effectiveness, and challenges of the ISMUBA program through in-depth interviews, direct observations, and documentation analysis. The results indicate that ISMUBA subjects significantly contribute to enhancing students' religious understanding and behavior, including improved discipline, moral attitudes, and engagement in worship practices. Teachers employ educational, social, and amaliah approaches to instill Islamic values, emphasizing both theoretical learning and practical application. Key supporting factors include an exemplary educational system, adequate facilities such as mosques and libraries, qualified teachers, and a supportive environment. However, challenges remain, including the heterogeneity of students' religious backgrounds and daily practices. This study concludes that the ISMUBA program effectively fosters moral development and religious consciousness among students, making it a vital component of Muhammadiyah’s educational mission to produce well-rounded individuals with strong religious and moral value.